Defect‐State Lasing in Photonic Lattices of Metal–Organic Microcavities. Issue 3 (4th February 2021) - Kliem, Mona; Kiel, Thomas; Kück, Malin; Meister, Stefan; Mischok, Andreas; Fröb, Hartmut; Busch, Kurt; Leo, Karl
Abstract : Photonic band structure engineering has developed into an important technique for controlling the emission and interaction of photons and polaritons in microcavities (MCs). Herein, lasing from defect states (DSs) in photonic Kronig–Penney structures embedded into metal–organic MCs is demonstrated. As compared to the more delocalized lasing states associated with photonic bands, these DSs exhibit improved lasing thresholds that lie even below the lasing threshold of the metal‐free cavity. The characteristics of these DSs are determined via full electrodynamic computations based on the discontinuous Galerkin time‐domain method. Abstract : Photonic band structure engineering has developed into an important technique for controlling the emission and interaction of photons and polaritons in microcavities (MCs). Herein, lasing from defect states in photonic Kronig–Penney‐like metal structures embedded into organic MC is demonstrated, exhibiting improved lasing thresholds that lie even below the lasing threshold of a metal‐free cavity.